Fructose: A Key Factor in the Development of Metabolic Syndrome and Hypertension - Zeid Khitan; Dong Hyun Kim (Journal of Nutrition and Metabolism)
Diabetes mellitus and the metabolic syndrome are becoming leading causes of death in the world. Identifying the etiology of diabetes is key to prevention. Despite the similarity in their structures, fructose and glucose are metabolized in different ways. Uric acid, a byproduct of uncontrolled fructose metabolism is known risk factor for hypertension. In the liver, fructose bypasses the two highly regulated steps in glycolysis, glucokinase and phosphofructokinase, both of which are inhibited by increasing concentrations of their byproducts. Fructose is metabolized by fructokinase (KHK). KHK has no negative feedback system, and ATP is used for phosphorylation. This results in intracellular phosphate depletion and the rapid generation of uric acid due to activation of AMP deaminase. Uric acid, a byproduct of this reaction, has been linked to endothelial dysfunction, insulin resistance, and hypertension. We present possible mechanisms by which fructose causes insulin resistance and suggest actions based on this association that have therapeutic implications.